Clases texturales de los suelos y su relación con la compactación en sistemas de cultivos de maíz (Zea mays L.) en el Ecuador - Vera Onofre, Marcelo Gabriel (2020)
Ecuador is said that the cultivation of corn was developed 6500 years ago, because investigations carried out from phytoliths in soil samples, reveal that in the Santa Elena Peninsula. Corn is a plant with an erect stem, depending on the variety, supported by a fibrous and compact root system consisting of a fasciculate or underground which fulfills the function of feeding the plant and the adventitious or aerial that serves as a support. The soil, we can distinguish different properties interacting with each other originating in turn a diversity of types of soils, depending on the incidence of each of them, the most important properties of the soil: texture, structure, infiltration, field capacity, point permanent wilting, available water Soil is a natural resource and its quality depends on sustainable management, good soil quality not only provides greater productivity in crops, in addition to maintaining environmental quality, consequently, plant, animal and Human Faced with the deterioration of soils in Ecuador, soil conservation techniques appear as a viable alternative, aimed at promoting their recovery and conservation, thus achieving the maintenance of their physical, chemical and biological conditions in order to preserve their health. and its quality in order to preserve its productive capacity indefinitely, to achieve agricultural sustainability.